A preparation method of composite antibacterial glaze

By forming Ag-Zn-Eu-La-Pr multivariate composite antibacterial system in antibacterial ceramics and introducing calcium phosphate and organic dispersants, the problems of unsatisfactory antibacterial effect and attenuation of antibacterial rate in existing antibacterial ceramics are solved, and high efficiency and long-term Effective antibacterial effect and improvement of glaze quality.

CN117510068BActive Publication Date: 2024-12-27JINGDEZHEN CERAMIC UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311729257.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2024-12-27
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

The antibacterial effect of existing antibacterial ceramics is not ideal and the antibacterial rate is fast attenuated, which cannot meet the market's demand for higher hygiene standards.

Method used

The preparation method of composite antibacterial glaze is adopted to form an Ag-Zn-Eu-La-Pr multivariate composite antibacterial system through zinc oxide in the base glaze and silver acetate, lanthanum oxide, praseodymium oxide, europium oxide, etc. in the composite antibacterial agent, and then the composite antibacterial system is formed. Calcium phosphate and organic dispersants are introduced into the antibacterial agent to form an efficient and long-acting antibacterial layer.

Benefits of technology

It significantly improves the antibacterial effect of the composite antibacterial glaze layer, extends the antibacterial time, realizes the advantages of efficient antibacterial and long-term antibacterial, and ensures the quality and safety of the glaze surface, meeting the needs of higher hygiene standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004609629790000051
    Figure BDA0004609629790000051
  • Figure BDA0004609629790000061
    Figure BDA0004609629790000061
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite antibacterial glaze, which consists of a basic glaze and a composite antibacterial agent. The Ag-Zn-Eu-La-Pr multi-component composite antibacterial system is formed by zinc oxide in the basic glaze and silver acetate, lanthanum oxide, praseodymium oxide and europium oxide in the composite antibacterial agent, thereby greatly improving the antibacterial effect of the composite antibacterial glaze layer. Meanwhile, calcium phosphate is introduced into the composite antibacterial agent and an organic dispersant is used for pretreatment, which not only ensures the quality of the glaze surface and improves the overall antibacterial effect of the glaze surface, but also prolongs the antibacterial time of the composite antibacterial glaze layer, so that the composite antibacterial glaze layer has the advantages of high-efficiency antibacterial and long-acting antibacterial. The composite antibacterial glaze is suitable for the field of building sanitary ceramics and can well meet the development of the market and people's demand for healthy life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibacterial glazes, and in particular to a preparation method of a composite antibacterial glaze. Background Art

[0002] As environmental awareness increases, people are more concerned about the environmental friendliness and health of products. As a decorative material that can inhibit the growth and spread of bacteria, antibacterial glaze ceramic products have excellent decorative properties and durability, which can meet people's needs for beauty and practicality at the same time. They are widely used in home decoration, hospital construction, public facilities and other fields, and have become an indispensable part of people's daily life. However, the antibacterial effect of antibacterial ceramics is not ideal at present, and the antibacterial rate decays quickly, which is not enough to meet the development of the market and people's demand for higher hygiene standards. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a composite antibacterial glaze, which is composed of a base glaze and a composite antibacterial agent. The Ag-Zn-Eu-La-Pr multi-component composite antibacterial system is formed by zinc oxide in the base glaze and silver acetate, lanthanum oxide, praseodymium oxide and europium oxide in the composite antibacterial agent, thereby greatly improving the antibacterial effect of the composite antibacterial glaze layer; at the same time, calcium phosphate is introduced into the composite antibacterial agent and an organic dispersant pretreatment method is adopted to ensure the quality of the glaze surface and improve the overall antibacterial effect of the glaze surface, and to extend the antibacterial time of the composite antibacterial glaze layer, so that it has the advantages of high-efficiency antibacterial and long-lasting antibacterial, thereby meeting people's demand for higher hygiene standards.

[0004] The purpose of the present invention is achieved through the following technical solutions:

[0005] The invention provides a method for preparing a composite antibacterial glaze. The composite antibacterial glaze is composed of a base glaze and a composite antibacterial agent. The raw materials of the base glaze are 28-32wt% of potassium feldspar, 25-28wt% of quartz, 8-13wt% of calcite, 5-7wt% of wollastonite, 5-7wt% of calcined kaolin, 2-4wt% of zinc oxide, 6-8wt% of talc, 2-3wt% of barium carbonate, 4-6wt% of porcelain stone, and 3-5wt% of zirconium silicate. The raw materials of the composite antibacterial agent are 0.9-1.2wt% of silver acetate, 1.5-2wt% of calcium phosphate, 0.3-0.6wt% of lanthanum oxide, 0.3-0.6wt% of praseodymium oxide, and 0.4-0.8wt% of europium oxide, and the usage amounts are relative to the base glaze. The preparation method comprises the following steps:

[0006] (1) After weighing and mixing the raw materials of the composite antibacterial agent according to the ratio, mixing with deionized water and an organic dispersant, and stirring to obtain a mixed solution; after heating, washing, filtering, drying, and sieving the mixed solution, a pre-antibacterial agent powder is obtained;

[0007] (2) After weighing and proportioning the basic glaze raw materials, mixing with the pre-antibacterial agent powder, wet ball milling and sieving to obtain a composite antibacterial glaze slurry;

[0008] (3) The composite antibacterial glaze slurry is applied to the surface of the ceramic body by dipping, and the obtained glaze body is dried and sintered at a temperature of 1250-1300° C., kept warm for 0.5-1.5 hours, and naturally cooled to obtain a composite antibacterial glaze layer.

[0009] Furthermore, the composition of the organic dispersant of the present invention is cellulose: fatty alcohol polyoxyethylene ether = 2-3: 1 by mass ratio, and the amount of the organic dispersant is 0.45-1.80wt% of the composite antibacterial agent. The heating in the step (1) is carried out in a water bath, and the temperature is kept at 90-100°C for 1.5-2h. In the step (2), ball milling is carried out according to material: ball: water = 1: 2-3: 0.5-0.8, and the ball milling time is 30-60min; the specific gravity of the composite antibacterial glaze slurry is 1.55-1.60kg / L. The glazing thickness in the step (3) is 0.7-1mm.

[0010] In the above scheme, the antibacterial rate of the composite antibacterial glaze layer of the present invention against Escherichia coli and Staphylococcus aureus is greater than 98.8%, and the antibacterial rate against the two bacteria is still above 95% after one year.

[0011] The present invention has the following beneficial effects:

[0012] (1) The ions of the rare earth elements europium, lanthanum, praseodymium and silver ions of the present invention are all positively charged. When they contact the cell membrane of microorganisms, Coulomb attraction occurs to firmly bind the two. On the one hand, the metal ions will penetrate the cell membrane and enter the bacteria to react with the hydrophobic groups and amino groups on the protein, so that the protein structure of the biological enzyme is destroyed, resulting in the inactivation and death of the bacteria; on the other hand, the negatively charged bacteria will be attracted by the metal ions of the composite antibacterial glaze layer, which will restrain the free movement of the bacteria and inhibit their respiratory function, resulting in the contact death of the bacteria. At the same time, the zinc oxide in the base glaze can play the role of a catalytic active center, which helps to form an Ag-Zn-Eu-La-Pr multi-component composite antibacterial system, thereby greatly improving the antibacterial effect of the composite antibacterial glaze layer.

[0013] (2) The method of introducing calcium phosphate into the composite antibacterial agent of the present invention and adopting organic dispersant pretreatment can not only alleviate the problem of poor glaze quality caused by excessive dissolution of elements such as europium, lanthanum, praseodymium, and silver, but also make the components of the composite antibacterial agent evenly dispersed on the glaze surface, which is beneficial to improving the overall antibacterial effect; at the same time, calcium phosphate has a certain chelating effect on metal ions, which can prevent more metal ions from being lost too quickly in the glaze layer, thereby extending the antibacterial time of the composite antibacterial glaze layer.

[0014] (3) The composite antibacterial glaze layer prepared by the present invention not only has the advantages of high efficiency and long-lasting antibacterial properties, but also has the functions of safety, non-toxicity and good glaze performance. Its application in the field of building sanitary ceramics can well meet the development of the market and people's demand for healthy life, and has positive significance for cutting off the transmission route of bacterial infection and improving people's living standards.

[0015] The present invention will be described in further detail below with reference to the embodiments. DETAILED DESCRIPTION

[0016] Embodiment 1:

[0017] The present embodiment provides a method for preparing a composite antibacterial glaze, wherein the composite antibacterial glaze is composed of a base glaze and a composite antibacterial agent; wherein the raw material composition of the base glaze is 28wt% of potassium feldspar, 25wt% of quartz, 13wt% of calcite, 7wt% of wollastonite, 5wt% of calcined kaolin, 4wt% of zinc oxide, 8wt% of talc, 2wt% of barium carbonate, 4wt% of porcelain stone, and 4wt% of zirconium silicate; the raw material composition of the composite antibacterial agent is 0.9wt% of silver acetate, 1.5wt% of calcium phosphate, 0.3wt% of lanthanum oxide, 0.3wt% of praseodymium oxide, and 0.4wt% of europium oxide, wherein the amount used is relative to the base glaze; the preparation method has the following steps:

[0018] (1) After weighing and proportioning the raw materials of the composite antibacterial agent, the raw materials are mixed with deionized water and an organic dispersant, and stirred at room temperature for 30 minutes to obtain a mixed solution; wherein the mass ratio of the composite antibacterial agent to deionized water is 2:1, and the mass ratio of the organic dispersant is cellulose to fatty alcohol polyoxyethylene ether is 2:1, and the amount thereof is 0.45wt% of the composite antibacterial agent; the mixed solution is slowly heated to 100°C in a water bath and kept warm for 1.5 hours, taken out, washed, filtered, dried, and passed through a 250-mesh standard sieve to obtain a pre-antibacterial agent powder;

[0019] (2) After weighing and mixing the above-mentioned basic glaze raw materials, the raw materials were mixed with the pre-antibacterial agent powder, and wet ball milled for 50 minutes according to the ratio of material: ball: water = 1:2:0.8, and passed through a 250-mesh standard sieve to obtain a composite antibacterial glaze slurry with a specific gravity of 1.55 kg / L;

[0020] (3) The composite antibacterial glaze slurry is applied to the surface of the ceramic body by dipping, and the glazing thickness is 0.7 mm. The obtained glaze body is dried and placed in a muffle furnace, and sintered at 1250°C for 0.5 h. After natural cooling, the composite antibacterial glaze layer is obtained.

[0021] Embodiment 2:

[0022] The present embodiment provides a method for preparing a composite antibacterial glaze, wherein the composite antibacterial glaze is composed of a base glaze and a composite antibacterial agent; wherein the raw materials of the base glaze are 30wt% of potassium feldspar, 26wt% of quartz, 11wt% of calcite, 6wt% of wollastonite, 6wt% of calcined kaolin, 3wt% of zinc oxide, 7wt% of talc, 3wt% of barium carbonate, 5wt% of porcelain stone, and 3wt% of zirconium silicate; the raw materials of the composite antibacterial agent are 1wt% of silver acetate, 1.5wt% of calcium phosphate, 0.4wt% of lanthanum oxide, 0.4wt% of praseodymium oxide, and 0.6wt% of europium oxide, and the amounts thereof are relative to the base glaze; the preparation method has the following steps:

[0023] (1) After weighing and proportioning the raw materials of the composite antibacterial agent, the raw materials are mixed with deionized water and an organic dispersant, and stirred at room temperature for 30 minutes to obtain a mixed solution; wherein the mass ratio of the composite antibacterial agent to deionized water is 2:1, and the mass ratio of the organic dispersant is cellulose to fatty alcohol polyoxyethylene ether is 3:1, and the amount thereof is 0.90wt% of the composite antibacterial agent; the mixed solution is slowly heated to 90°C in a water bath and kept warm for 2 hours, taken out, washed, filtered, dried, and passed through a 250-mesh standard sieve to obtain a pre-antibacterial agent powder;

[0024] (2) After weighing and mixing the above-mentioned basic glaze raw materials, the raw materials were mixed with the pre-antibacterial agent powder, and wet ball milled for 60 minutes according to the ratio of material: ball: water = 1: 3: 0.5, and passed through a 250-mesh standard sieve to obtain a composite antibacterial glaze slurry with a specific gravity of 1.57 kg / L;

[0025] (3) The composite antibacterial glaze slurry is applied to the surface of the ceramic body by dipping, and the glazing thickness is 0.8 mm. The obtained glaze body is dried and placed in a muffle furnace for sintering at 1270°C for 1 hour. After natural cooling, the composite antibacterial glaze layer is obtained.

[0026] Embodiment three:

[0027] The present embodiment provides a method for preparing a composite antibacterial glaze, wherein the composite antibacterial glaze is composed of a base glaze and a composite antibacterial agent; wherein the raw material composition of the base glaze is 31wt% of potassium feldspar, 27wt% of quartz, 9wt% of calcite, 5wt% of wollastonite, 7wt% of calcined kaolin, 3wt% of zinc oxide, 6wt% of talc, 3wt% of barium carbonate, 6wt% of porcelain stone, and 3wt% of zirconium silicate; the raw material composition of the composite antibacterial agent is 1.1wt% of silver acetate, 2wt% of calcium phosphate, 0.5wt% of lanthanum oxide, 0.5wt% of praseodymium oxide, and 0.6wt% of europium oxide, wherein the amount used is relative to the base glaze; the preparation method has the following steps:

[0028] (1) After weighing and proportioning the raw materials of the composite antibacterial agent, the raw materials are mixed with deionized water and an organic dispersant, and stirred at room temperature for 30 minutes to obtain a mixed solution; wherein the mass ratio of the composite antibacterial agent to deionized water is 2:1, and the composition of the organic dispersant is cellulose to fatty alcohol polyoxyethylene ether according to the mass ratio of 2:1, and the amount thereof is 1.35wt% of the composite antibacterial agent; the mixed solution is slowly heated to 95°C in a water bath and kept warm for 2 hours, taken out, washed, filtered, dried, and passed through a 250-mesh standard sieve to obtain a pre-antibacterial agent powder;

[0029] (2) After weighing and mixing the above-mentioned basic glaze raw materials, the raw materials were mixed with the pre-antibacterial agent powder, and wet ball milled for 30 minutes according to the ratio of material: ball: water = 1: 2: 0.7, and passed through a 250-mesh standard sieve to obtain a composite antibacterial glaze slurry with a specific gravity of 1.59 kg / L;

[0030] (3) The composite antibacterial glaze slurry is applied to the surface of the ceramic body by dipping, and the glazing thickness is 0.9 mm. The obtained glaze body is dried and placed in a muffle furnace for sintering at 1290°C for 1 hour. After natural cooling, the composite antibacterial glaze layer is obtained.

[0031] Embodiment 4:

[0032] The present embodiment provides a method for preparing a composite antibacterial glaze, wherein the composite antibacterial glaze is composed of a base glaze and a composite antibacterial agent; wherein the raw material composition of the base glaze is 32wt% of potassium feldspar, 28wt% of quartz, 8wt% of calcite, 5wt% of wollastonite, 6wt% of calcined kaolin, 2wt% of zinc oxide, 6wt% of talc, 2wt% of barium carbonate, 6wt% of porcelain stone, and 5wt% of zirconium silicate; the raw material composition of the composite antibacterial agent is 1.2wt% of silver acetate, 2wt% of calcium phosphate, 0.6wt% of lanthanum oxide, 0.6wt% of praseodymium oxide, and 0.8wt% of europium oxide, wherein the amount used is relative to the base glaze; the preparation method has the following steps:

[0033] (1) After weighing and proportioning the raw materials of the composite antibacterial agent, the raw materials are mixed with deionized water and an organic dispersant, and stirred at room temperature for 30 minutes to obtain a mixed solution; wherein the mass ratio of the composite antibacterial agent to deionized water is 2:1, and the mass ratio of the organic dispersant is cellulose to fatty alcohol polyoxyethylene ether is 3:1, and the amount thereof is 1.80wt% of the composite antibacterial agent; the mixed solution is slowly heated to 100°C in a water bath and kept warm for 1.5 hours, taken out, washed, filtered, dried, and passed through a 250-mesh standard sieve to obtain a pre-antibacterial agent powder;

[0034] (2) After weighing and mixing the above-mentioned basic glaze raw materials, the raw materials were mixed with the pre-antibacterial agent powder, and wet ball milled for 40 minutes according to the ratio of material: ball: water = 1: 3: 0.6, and passed through a 250-mesh standard sieve to obtain a composite antibacterial glaze slurry with a specific gravity of 1.60 kg / L;

[0035] (3) The composite antibacterial glaze slurry is applied to the surface of the ceramic body by dipping, and the glazing thickness is 1 mm. After drying, the obtained glaze body is placed in a muffle furnace and sintered at 1300°C for 1.5 hours. After natural cooling, the composite antibacterial glaze layer is obtained.

[0036] The raw materials used in the embodiments of the present invention, the zinc oxide and barium carbonate in the basic glaze, and the silver acetate, calcium phosphate, lanthanum oxide, praseodymium oxide, and europium oxide of the composite antibacterial agent are all chemically pure raw materials (ZnO, BaCO 3 , CH 3 COOAg, Ca 3 (PO) 4 ,La 2 O 3 , Pr 6 O 11 、Eu 2 O 3 ≥99.5%). The chemical compositions of the remaining raw materials are shown in Table 1.

[0037] Table 1 Chemical composition of the basic glaze raw materials of the present invention (wt%)

[0038]

[0039] Antibacterial performance test:

[0040] The test was conducted according to the test method of JC / T 897-2014 "Antibacterial Performance of Antibacterial Ceramic Products". Taking ordinary antibacterial ceramics as comparative examples, the antibacterial performance test results of the composite antibacterial glaze layer prepared in each embodiment of the present invention and the ordinary antibacterial ceramic glaze layer of the comparative example are shown in Table 2.

[0041] Table 2 Antibacterial performance test results of the embodiments of the present invention and the comparative examples

[0042]

[0043] It can be seen from the test results in Table 2 that the composite antibacterial glaze layer prepared by the embodiment of the present invention has an excellent antibacterial effect, and the antibacterial rates against Escherichia coli and Staphylococcus aureus are both about 99%, far exceeding the national standard of 90%, while the antibacterial rate of ordinary antibacterial ceramics is only about 97%; after one year, the antibacterial rate of ordinary antibacterial ceramics against the two bacteria has weakened to about 81%, far below the national requirement of 90%, while the antibacterial rate of the present invention against Escherichia coli and Staphylococcus aureus after one year is still above 95%, far exceeding the national standard; compared with the antibacterial rate after two years, ordinary antibacterial ceramics almost have no antibacterial effect, while the antibacterial rate of the present invention against the two bacteria is still more than 50%, and the antibacterial effect is more lasting.

Claims

1. A method for preparing a composite antibacterial glaze, characterized in that: The composite antibacterial glaze is composed of a base glaze and a composite antibacterial agent; the raw materials of the base glaze are 28-32wt% of potassium feldspar, 25-28wt% of quartz, 8-13wt% of calcite, 5-7wt% of wollastonite, 5-7wt% of calcined kaolin, 2-4wt% of zinc oxide, 6-8wt% of talc, 2-3wt% of barium carbonate, 4-6wt% of porcelain stone, and 3-5wt% of zirconium silicate; the raw materials of the composite antibacterial agent are used in amounts relative to the base glaze: 0.9-1.2wt% of silver acetate, 1.5-2wt% of calcium phosphate, 0.3-0.6wt% of lanthanum oxide, 0.3-0.6wt% of praseodymium oxide, and 0.4-0.8wt% of europium oxide; the preparation method comprises the following steps: (1) After weighing and mixing the raw materials of the composite antibacterial agent in a certain proportion, the raw materials are mixed with deionized water and an organic dispersant and stirred to obtain a mixed solution, wherein the composition of the organic dispersant is cellulose: fatty alcohol polyoxyethylene ether in a mass ratio of 2 to 3:1, and the amount of the organic dispersant is 0.45 to 1.80 wt % of the composite antibacterial agent; the mixed solution is heated, washed, filtered, dried, and sieved to obtain a pre-antibacterial agent powder, wherein the heating is carried out in a water bath and the mixture is kept warm at 90 to 100° C. for 1.5 to 2 hours; (2) After weighing and mixing the basic glaze raw materials, the raw materials are mixed with the pre-antibacterial agent powder, and wet ball milled according to the ratio of material: ball: water = 1: 2-3: 0.5-0.8, the ball milling time is 30-60 min, and after sieving, a composite antibacterial glaze slurry with a specific gravity of 1.55-1.60 kg / L is obtained; (3) The composite antibacterial glaze slurry is applied to the surface of the ceramic body by dipping, and the obtained glaze body is dried and sintered at a temperature of 1250-1300° C., kept warm for 0.5-1.5 hours, and naturally cooled to obtain a composite antibacterial glaze layer. The antibacterial rates of the composite antibacterial glaze layer against Escherichia coli and Staphylococcus aureus are both greater than 98.8%, and the antibacterial rates against the two bacteria are still above 95% after one year.

2. The method for preparing the composite antibacterial glaze according to claim 1, characterized in that: The glazing thickness in step (3) is 0.7 to 1 mm.